Extraction of 3D Information from Circular Array Measurements for Auralization with Wave Field Synthesis. (12th April 2007) - de Vries de Vries, Diemer Diemer; Hörchens Hörchens, Lars Lars; Grond Grond, Peter Peter
Abstract : The state of the art of wave field synthesis (WFS) systems is that they can reproduce sound sources and secondary (mirror image) sources with natural spaciousness in a horizontal plane, and thus perform satisfactory 2D auralization of an enclosed space, based on multitrace impulse response data measured or simulated along a 2D microphone array. However, waves propagating with a nonzero elevation angle are also reproduced in the horizontal plane, which is neither physically nor perceptually correct. In most listening environments to be auralized, the floor is highly absorptive since it is covered with upholstered seats, occupied during performances by a well-dressed audience. A first-order ceiling reflection, reaching the floor directly or via a wall, will be severely damped and will not play a significant role in the room response anymore. This means that a spatially correct WFS reproduction of first-order ceiling reflections, by means of a loudspeaker array at the ceiling of the auralization reproduction room, is necessary and probably sufficient to create the desired 3D spatial perception. To determine the driving signals for the loudspeakers in the ceiling array, it is necessary to identify the relevant ceiling reflection(s) in the multichannel impulse response data and separate those events from the data set. Two methods are examined to identify, separate, and reproduce the relevant reflections: application of the Radon transform, and decomposition of the data into cylindrical harmonics. Application to synthesized and measured data shows that both methods in principle are able to identify, separate, and reproduce the relevant events.